Black Boys’ and Young Men’s Experiences with Criminal Justice and Desistance in England and Wales: A Literature Review - Laura Robertson; John Peter Wainwright (Genealogy, 2020)
Black boys and young men are over-represented in the youth and adult justice systems in England and Wales. Despite the Lammy Review (2017) into the treatment of and outcomes for Black, Asian, and minority ethnic individuals (BAME) in the criminal justice system, the disproportionate numbers of Black boys and young men at all stages of the system continue to rise. There has been limited qualitative research of Black boys’ and young men’s experiences with the justice system in England and Wales. In particular, there is a lack of evidence on their experiences with sentencing and courts. What is known tends to focus on Black, Asian, and minority ethnic and/or Muslim men’s experiences more generally. A lack of critical understanding of the specific experiences of desistance by young Black men has been criticised in the literature. Set in this context, this review of UK literature focuses on the following questions: (1) What are Black boys’ and young Black men’s experiences with the youth and criminal justice systems in England and Wales? (2) What does research tell us specifically about their experiences with desistance?